2021
DOI: 10.3390/su13041665
|View full text |Cite
|
Sign up to set email alerts
|

How Chinese Students’ Travel Constraints Influence Their Travel Intentions in Thailand: Moderating Role of Cross-Cultural Adaptation

Abstract: This study clarified the controversial travel constraints in the tourism literature and test the moderating role of cross-cultural adaptation (CCA) on the relationship between travel constraints and travel intention. In this study, 897 questionnaires were collected from Chinese students studying in Thailand. Structural equation modeling was adopted to test the proposed model, and the moderating effect of CCA was examined via multigroup analysis. Results demonstrated that interpersonal constraints positively in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
2
2
0
Order By: Relevance
“…Rather, it was intrapersonal constraints, such as lack of tourists' knowledge and interest, that adversely impacted their intention to revisit heritage destinations. This confirms previous empirical evidence (Khan et al, 2019;Shores et al, 2007;Wong and Kuo, 2021) for the greatest impact of psychological travel constraints on travel preference and continuity. These findings highlight the role of destination managers in developing strategies that emphasise the unique aspects of local attractions and cater to tourists' needs.…”
Section: Theoretical Implicationssupporting
confidence: 90%
“…Rather, it was intrapersonal constraints, such as lack of tourists' knowledge and interest, that adversely impacted their intention to revisit heritage destinations. This confirms previous empirical evidence (Khan et al, 2019;Shores et al, 2007;Wong and Kuo, 2021) for the greatest impact of psychological travel constraints on travel preference and continuity. These findings highlight the role of destination managers in developing strategies that emphasise the unique aspects of local attractions and cater to tourists' needs.…”
Section: Theoretical Implicationssupporting
confidence: 90%
“…This may affect their plans to travel in the new normal. This finding is in line with the study done by [51][52][53]. However, it is in contrast with previous research done by [54].…”
Section: Findings and Discussionsupporting
confidence: 88%
“…In the past three decades, many studies have adopted the LCM to examine how travel constraints influence travel intentions, and much knowledge has been drawn from these research ( Mei and Lantai, 2018 ; Yang and Tung, 2018 ; Jian et al, 2021 ). It is generally recognized that travel constraints, as obstacles and inhibitors, significantly affect individuals’ preferences and participation in tourism activities ( Wong and Kuo, 2021 ). Therefore, most relevant studies assume that travel constraints have a negative impact on travel intentions ( Nyaupane and Andereck, 2008 ; Hung and Petrick, 2012 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These constraints are considered the most influential factors restricting individuals’ participation in leisure activities ( Fredman and Heberlein, 2005 ). Specifically, it is found that prospective travelers’ intentions to travel will decrease under the negative impacts of structural constraints ( Lai et al, 2013 ; Wong and Kuo, 2021 ). Conversely, Khan et al (2019b) concluded that structural constraints have no significant relationship with travel intentions as Chen et al (2021) explained that structural constraints are negotiable.…”
Section: Literature Reviewmentioning
confidence: 99%